2020
DOI: 10.26452/ijrps.v11ispl4.4416
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of α -glucosidase inhibitory activity and phytochemical analysis of Piper crocatum Ruiz & Pav. leaves ethanol extract

Abstract: α-Glucosidase is an enzymes group that playing essential roles in the digestion of polysaccharide. Inhibitor of a-glucosidase can decrease polysaccharide digestion rate and therefore plays a significant function in preventing the development of diabetes (type 2). Piper crocatum Ruiz & Pav. is an essential herb applied traditionally in Indonesia to treat diabetes mellitus. This work evaluated the a-glucosidase inhibitory activity of P. crocatum leaves ethanol extract. Phytochemical component of the extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Antihyperglycemic activity in vitro showed that ethyl acetate fraction of the red betel has an IC 50 value of 743.80 μg/mL with a competitive inhibitory mechanism to the alpha(α)-glucosidase ( Weni 2018 ). In addition, red betel ethanol extract exhibited a competitive inhibition for α-glucosidase, similar to acarbose on α-glucosidase inhibition ( Alfarabi et al . 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antihyperglycemic activity in vitro showed that ethyl acetate fraction of the red betel has an IC 50 value of 743.80 μg/mL with a competitive inhibitory mechanism to the alpha(α)-glucosidase ( Weni 2018 ). In addition, red betel ethanol extract exhibited a competitive inhibition for α-glucosidase, similar to acarbose on α-glucosidase inhibition ( Alfarabi et al . 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stilbene, phenol, linolenic acid, phytosteroid and α-tocopherol are bioactive compounds contained in the ethanol extract of red betel leaves. Stilbene and phenol have α-glucosidase inhibitory activity ( Alfarabi et al . 2021 ).…”
Section: Introductionmentioning
confidence: 99%